Comparison of the structural levels in the academic writing of the university text - Muñoz Urbina, María Consuelo (2019)
In this research an analysis was made about the academic texts written by university students of education and psychology of a Peruvian university in order to determine and analyze the differences on their academic writing. To collect information on the academic writing of the students, a rubric was elaborated with a segmentation method of differentiated scales between superstructure, macrostructure, microstructure, stylistics and rhetoric, based on Van Dijk's theory. The sample was formed by 74 students from two faculties: 47% psychology students and 53% education. The results on the composition of an academic text indicated the poor writing in the students of both careers, although those of psychology obtained higher scores. In addition, statistical differences were found in the superstructure, microstructure and style of the texts they produced. Finally, it is recommended the need to change the traditional teaching of writing, which is still deficient in Peru and focus on developing levels of thought in the text levels of Van Dijk for the development of efficient academic writing.